Intravesical recurrence factors and outcome after radical nephroureterectomy for upper tract urothelial carcinoma: Multivariate analysis with propensity score matching - Zhao, Hang; Jiao, Binbin; Liu, Kunpeng; Luo, Zhenkai; Ding, Zhenshan; Lai, Shicong; Ren, Jian; Zhang, Guan (Frontiers in Oncology, 2022)
Abstract Objective: The risk factors for intravesical recurrence (IVR) after radical nephroureterectomy (RNU) in patients with upper tract urothelial carcinoma (UTUC) remain inconsistent and unclear. Thus, the risk factors of IVR after RNU and the prognostic significance of the risk indicators were explored herein. Methods: We retrospectively analyzed UTUC patients upon RNU in our center from January 2009 to December 2019. After propensity score matching, 139 patients were included in this study. Univariate and multivariate Cox proportional hazard regressions were used to estimate the hazard ratio and 95% confidence intervals. Overall survival (OS), cancer-specific survival (CSS) and recurrence-free survival (RFS) were measured using the Kaplan–Meier curve with a log-rank test. A P-value < 0.05 was considered statistically significant. Results: We included 139 patients with a median follow-up of 42 months, of which 48 patients had an intravesical recurrence. Multivariate Cox regression analysis showed cytological abnormalities in urine (HR=3.101, P=0.002), hydronephrosis (HR=1.852, P=0.042), adjuvant chemotherapy (HR=0.242, P<0.001), and previous history of bladder cancer (HR=5.51, P<0.001) were independent risk factors for IVR. As for clinical outcomes, OS and CSS suggested disadvantages in patients with IVR compared with patients without recurrence (P=0.042 for OS, P<0.0001 for CSS), OS of patients with abnormal urine cytology and OS and CSS of patients receiving adjuvant chemotherapy did not present clinical significance, and other risk factors all affected the clinical outcome. Conclusion: In this propensity-score matching study, cytological abnormality of urine, hydronephrosis, adjuvant chemotherapy and previous history of bladder cancer were shown to be independent risk factors for IVR. Moreover, risk factors also influence clinical outcomes, thereby rendering it necessary to adopt more active postoperative surveillance and treatment strategies for these patients, which may help improve treatment outcomes.